2015
DOI: 10.4028/www.scientific.net/amr.1120-1121.939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn on the Microstructure and Hardness of Gear Steel Treated by Quenching and Partitioning Process

Abstract: By adding Mn into SAE8620 gear steel, the effect of Mn on the microstructure and hardness of steel treated by quenching and partitioning process is investigated in this research. Microstructure is observed. Hardness is measured, after that it is converted into tensile strength. And the content of austenite is determined by X-ray diffraction analysis. It is found that higher content of Mn increases the content of martensite and reduces that of blocky ferrite and also leads to higher hardness of steel. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The results showed that when initial quenching after austenitisation is done up to QT opt , a substantial amount of retained austenite can be stabilised at RT after the Q&P processing. A comparison between the calculated, using Speer's model, and the actual amount of retained austenite estimated using XRD analysis as a function of QT is shown in Figure 4(b) [62]. The variation of the actual amount of retained austenite with QT is in qualitative agreement with trends predicted using Speer's model.…”
Section: Optimum Quenching Temperature (Qt Opt )supporting
confidence: 66%
See 2 more Smart Citations
“…The results showed that when initial quenching after austenitisation is done up to QT opt , a substantial amount of retained austenite can be stabilised at RT after the Q&P processing. A comparison between the calculated, using Speer's model, and the actual amount of retained austenite estimated using XRD analysis as a function of QT is shown in Figure 4(b) [62]. The variation of the actual amount of retained austenite with QT is in qualitative agreement with trends predicted using Speer's model.…”
Section: Optimum Quenching Temperature (Qt Opt )supporting
confidence: 66%
“…The observed discrepancies between the experimental (literature data) and calculated (by CCE and Speer's models) amount of retained austenite and its carbon content after the Q&P processing have been attributed mainly to the carbide precipitation inside martensite and bainite formation during partitioning. In some studies on the Q&P process, the amount of retained austenite and its carbon content was found to decrease [8,31] and (b) comparison between the QT opt and the corresponding retained austenite fraction predicted using Speer's methodology and the experimental values obtained using XRD analysis [62]. The symbols used here have already been defined earlier in this discussion.…”
Section: Optimum Quenching Temperature (Qt Opt )mentioning
confidence: 99%
See 1 more Smart Citation